Improving consumption rate estimates by incorporating wild activity into a bioenergetics model. Issue 8 (4th March 2016) - Brodie, Stephanie; Taylor, Matthew D.; Smith, James A.; Suthers, Iain M.; Gray, Charles A.; Payne, Nicholas L.
Abstract : The contribution of activity to an animal's energy budget is an important parameter when estimating consumption, yet activity is usually measured in captive animals. We calculated the consumption rate of a free‐ranging marine predator (yellowtail kingfish, Seriola lalandi ) by integrating the energetic cost of free‐ranging activity into a bioenergetics model. Incorporating field‐derived activity into bioenergetics models probably provided more realistic estimates of consumption rate compared with the traditional methods, which may further our understanding of trophic interactions that underpin ecosystem‐based fisheries management. Abstract: Consumption is the basis of metabolic and trophic ecology and is used to assess an animal's trophic impact. The contribution of activity to an animal's energy budget is an important parameter when estimating consumption, yet activity is usually measured in captive animals. Developments in telemetry have allowed the energetic costs of activity to be measured for wild animals; however, wild activity is seldom incorporated into estimates of consumption rates. We calculated the consumption rate of a free‐ranging marine predator (yellowtail kingfish, Seriola lalandi ) by integrating the energetic cost of free‐ranging activity into a bioenergetics model. Accelerometry transmitters were used in conjunction with laboratory respirometry trials to estimate kingfish active metabolic rate in the wild. These field‐derived consumption rate estimates were compared with those estimated by two traditional bioenergetics methods. The first method derived routine swimming speed from fish morphology as an index of activity (a "morphometric" method), and the second considered activity as a fixed proportion of standard metabolic rate (a "physiological" method). The mean consumption rate for free‐ranging kingfish measured by accelerometry was 152 J·g −1 ·day −1, which lay between the estimates from the morphometric method ( μ  = 134 J·g −1 ·day −1 ) and the physiological method ( μ  = 181 J·g −1 ·day −1 ). Incorporating field‐derived activity values resulted in the smallest variance in log‐normally distributed consumption rates ( σ  = 0.31), compared with the morphometric ( σ  = 0.57) and physiological ( σ  = 0.78) methods. Incorporating field‐derived activity into bioenergetics models probably provided more realistic estimates of consumption rate compared with the traditional methods, which may further our understanding of trophic interactions that underpin ecosystem‐based fisheries management. The general methods used to estimate active metabolic rates of free‐ranging fish could be extended to examine ecological energetics and trophic interactions across aquatic and terrestrial ecosystems.